Quercetin and Luteolin Improve the Anticancer Effects of 5-Fluorouracil in Human Colorectal Adenocarcinoma In Vitro Model: A Mechanistic Insight. - Erdoğan, Mehmet Kadir; Ağca, Can Ali; Aşkın, Hakan (Nutrition & Cancer, 2022)
The aim of this study was to investigate the antitumor effects of quercetin and luteolin combined with 5-Fluorouracil (5-FU) in HT-29 human colorectal cancer cells. Cell viability induced by quercetin, luteolin and combination of these compounds with 5-FU were determined by MTT assay, also Cell death detection Elisa assay and fluorescence microscopy were performed to investigate apoptotic effects. Hu-VEGF Elisa assay was employed to determine the effects of treatments on angiogenesis. Western blot and qRT-PCR analysis were performed to investigate effects on p53, Bax, Bcl-2, p38 MAPK, mTOR, PTEN, and Akt proteins and genes. The results indicated that quercetin, luteolin and combinations of these compounds with 5-FU inhibited the growth of HT 29 cells. Compared to the control, apoptosis were triggered 8.1 and 10.1 fold in HT-29 cells, that treated with quercetin + 5-FU and luteolin + 5-FU, respectively. VEGF amount significantly decreased by combined treatments. qRT-PCR and western blot results demonstrated that quercetin, luteolin and the combinations of these flavonoids with 5-FU, modulate the apoptotic pathways in HT-29 cells. The increase in p53, Bax, p38 MAPK, and PTEN gene expression levels compared to the control group was 1.71, 1.42, 3.26, and 3.29-fold with 5-FU + L treatment, respectively, while this increase was 8.43, 1.65, 3.55, and 3.54-fold with 5-FU + Q treatment, respectively. In addition, when the anti-apoptotic Bcl-2, mTOR, and Akt gene expression levels were normalized as 1 in the control group, they were 0.28, 0.41, and 0.22 with 5-FU + L treatment, and 0.32, 0.46, and 0.39, respectively, with 5-FU + Q treatment. These findings suggested that quercetin and luteolin synergistically enhanced the anticancer effect of 5-FU in HT 29 cells and may therefore minimize the toxic effects of 5-FU in the clinical treatment of colorectal cancer.